Evaluation of ultrasound assisted and conventional methods for production of olive pomace oil enriched in sterols and squalene. (January 2019) - Chanioti, Sofia; Tzia, Constantina
Abstract: This study highlights the extraction of olive pomace oil enriched in sterols and squalene by using two methods: ultrasound-assisted extraction (UAE) and conventional extraction by various solvent systems. UAE was performed to examine the effect of temperature and solid/liquid ratio on the extraction of these minor compounds using hexane and the optimal conditions were found:1.399 mg/g at 60 °C and 1/12 g/mL for β-sitosterol; 0.220 mg/g at 55 °C and 1/10 g/mL for campesterol; 0.105 mg/g at 50 °C and 1/12 g/mL for stigmasterol and 4.575 mg/g at 60 °C and 1/12 g/mL for squalene recovery. Conventional extraction by various alternative solvent systems (hexane, isopropanol and their mixtures) were used and their effect on the sterols and squalene extraction under Soxhlet (SE) conditions was also investigated. The hexane:isopropanol 3:2 (H:I 3:2) mixture achieved high sterols and squalene recovery (total sterols: 1.706 mg/g; squalene: 5.217 mg/g), which extracted also the highest oil (13.70%) and unsaponifiable matter (4.92%). Comparing the two methods, it was revealed that the application of UAE led to oils with higher sterols and squalene content than the ones obtained by SE using hexane as solvent and with almost similar content with that by SE using H:I 3:2. Highlights: Two methods were evaluated for the extraction of olive pomace oil enriched in sterols and squalene. Ultrasound assisted extraction (UAE) was performed and optimized. Conventional extraction (SE) by alternative solvent systems (Hexane:Isopropanol mixtures – H:I) was applied. UAE led to oils with higher sterols and squalene content than SE. Hexane:Isopropanol 3:2 resulted in almost similar content of sterols and squalene to UAE.